Health risk assessment of exposure to natural radionuclides and heavy metals in indigenous eyeliners used in Benue State, Nigeria - Audu Moses Owoicho; Julius Tsaviv Nyiayem; Agada Inikpi Ojochenemi; Aondohemba Achu Paschal; Eneji Ishaq Shaibu (African Scientific Reports, 2026)
This study investigates natural radionuclides (NRs) and heavy metals (HMs) in locally produced eyeliners. Untreated (market-bought) and treated (laboratory-prepared) eyeliners were analysed for NRs and HMs using a NaI(Tl) detector and an atomic absorption spectrophotometer. Potential health risks from exposure were assessed using the margin of safety (MoS), systemic exposure dose (SED), carcinogenic risk, and radiological health indices. Results revealed activity concentrations of 40K, 238U, and 232Th as 44.87 ± 2.40, 0.98 ± 0.07, and 6.07 ± 0.34 Bq kg-1 in the untreated eyeliner and 43.58 ± 2.38, 1.93 ± 0.20, and 7.81 ± 0.44 Bq kg-1 in the treated eyeliner, respectively. The observed cancer risk from exposure to NRs was within the safe range (1 x 10-6 -1 x 10-4) for cosmetic products; hence, no radiological health risk from exposure to the eyeliners was indicated. Furthermore, significant reductions were observed in the concentrations of Cd, Co, Cr, and Pb in the treated eyeliner, except for Ni. This was ascertained from the statistical analysis. This indicates improvement, as the impact of Ni may be less significant than that of Pb, especially in children. The observed SED values imply that the effects of HMs in the sampled eyeliners on children were more severe than on adults. To mitigate the impact of HMs, prolonged exposure should be discouraged to avoid bioaccumulation. This study provides scientific insight into the concentrations of NRs and HMs in locally produced eyeliners.